Fetal and maternal outcomes in patients with tetralogy of Fallot. (14th October 2021) - Mano, T; Ferreira, V; Moreira, R I; Teixeira, B; Agapito, A; Rito, T; Pinto, F; Cruz Ferreira, R; De Sousa, L
Abstract: Introduction: Women with tetralogy of Fallot (TOF) have an increased risk of adverse cardiac and neonatal events during pregnancy. The aim was to assess fetal and maternal outcomes in patients (pts) with uncorrected and corrected TOF. Methods: Retrospective analysis of cardiological and obstetric data in women with TOF followed at our institution. Pregnancy and neonatal outcomes were compared in patients (pts) submitted to corrective surgery vs pts with no previous intervention and in pts with or without cyanosis. Results: 51 women (median age 27 years; median number of previous interventions of 2), 22% with cyanosis, who experienced 126 pregnancies resulting in 73 live births A previous corrective surgery was found in 78% (40 pts), while 4% (2 pts) had previous palliative surgery and 18% (9 pts) no previous procedure. We found that women that were not submitted to previous intervention had a significant higher incidence of preterm birth (56% vs 17.5%, p=0.029), spontaneous abortion (56% vs 10%, p=0.006) and stillbirth (22% vs 0%). No difference was found for obstetric complications between groups. Cyanotic pts also demonstrated higher incidence of low birth weight (LBW) (36% vs 7.5%, p=0.031), preterm birth (54% vs 17.5%, p=0.021), spontaneous abortion (55% vs 10%, p=0.004) and stillbirth (18% vs 0%). There were no cardiac complications during pregnancy nor evident deterioration on cardiac status. Congenital heart disease was reported in 2 infants (3% of live births). Conclusions: Pregnancy is well tolerated in pts with TOF. In our population, even in uncorrected TOF and in pts with cyanosis, there were no cardiac complications during pregnancy, although those pts had worse fetal outcomes. An explanation for the low incidence of cardiac events may be less severe forms of the disease, allowing survival into adulthood without intervention. FUNDunding Acknowledgement: Type of funding sources: None.